[OA213] Implementation and in-phantom testing of a free Monte Carlo software for CT dose calculation. (August 2018) - Boschini, Alessio; Riccardi, Lucia; Monte, Francesca De; Zandonà, Roberto; Paiusco, Marta
Abstract : Purpose: This study is aimed to implement and validate a free Monte Carlo system (GMctdospp) for dose calculation in CT scans. Methods: GMctdospp is an open source software developed by Institute of Medical Physics and Radiation Protection[1] . It can be downloaded and installed on a local server, to perform dosimetric calculations from CT images. Model of the CT equipment used for measurements (Siemens Somatom Definition AS) was provided within the software. The CT number to density calibration curve was introduced in the configuration data, to accurately match the HU ranges of simulated materials. Dose values at center and peripheral positions of a CTDI head phantom were measured with a pencil ionization chamber for different beam collimations (5 mm–10 mm–14.4 mm–19.2 mm), and compared to those simulated by the MC software. To define volumes for dose calculation, VOIs were obtained in the CT images by contouring the sensitive volume of the detector. In order to provide an estimation for skin dose, a second set of measurements was performed by scanning the head of a Rando phantom with gafchromic films placed on its surface in different positions (nose, occipital zone, temporal left and right). Images were acquired with a standard helical head routine protocol (120 kV, 19.2 mm collimation) and fixed tube current (200 mA). Dose values measured by the gafchromic films were then compared to those resulting from MC simulations based on the acquired CT images. Results: The accuracy of the MC simulated dose values was variable. For CTDI head phantom, the difference between measured and simulated dose ranged between 2% and 19%. For skin dose an average agreement of about 13% was found between measured and calculated values. Conclusions: Gmctdospp free MC software can be effectively used to calculate absorbed dose in CT scans acquired with fixed mA. Given the variability we observed in accuracy of the simulated dose values, further work is required in our institution, in order to validate the MC software.